PEMANFAATAN MEDIA BERMAIN ULAR TANGGA DALAM PENGEMBANGAN BERHITUNG PADA KELOMPOK A TK TUNAS MEKAR SURABAYA - INSANI, AULIA (Buana Pendidikan, 2020)
This research was conducted against the background of underdeveloped children's ability to count numbers 1-20. The purpose of this study is to get a picture of the use of snakes and ladders media in developing the ability to count numbers and understand the function of playing instruments used as media in learning with play activities. Play is the most influential factor in children's self development, one of which is cognitive development. In this activity the method used is giving tasks and direct practice with observation as an assessment tool. The subjects of the study were all students of group A Tunas Mekar Kindergarten in Surabaya in the academic year 2019-2020 with a total of 20 participants. The results of the descriptive analysis revealed: The ability to count numbers before using the media was not optimal, in the assessment scores achieved from each indicator of completeness learning below the average, while using the media snakes and ladders experienced a very optimal development in the assessment scores achieved from each indicator of mastery learning very well.